2013
DOI: 10.1371/journal.pntd.0002069
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi I and IV Stocks from Brazilian Amazon Are Divergent in Terms of Biological and Medical Properties in Mice

Abstract: BackgroundIn the Brazilian Amazon, clinical and epidemiological frameworks of Chagas disease are very dissimilar in relation to the endemic classical areas of transmission, possibly due to genetic and biological characteristics of the circulating Trypanosoma cruzi stocks. Twenty six T. cruzi stocks from Western Amazon Region attributed to the TcI and TcIV DTUs were comparatively studied in Swiss mice to test the hypothesis that T. cruzi clonal structure has a major impact on its biological and medical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 60 publications
1
26
0
3
Order By: Relevance
“…Because the infection caused by different T. cruzi strains has specific evolution and mortality rates in a mouse model [43], we infected mice with a distinct parasite inoculum for each strain to reach the chronic phase when the sera were collected. Thus, to evaluate whether the differences in reactivity observed in the ELISA experiments were dependent on the inoculum, we tested the reactivity of sera from mice infected with 50, 100, or 500 CL Brener trypomastigotes (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Because the infection caused by different T. cruzi strains has specific evolution and mortality rates in a mouse model [43], we infected mice with a distinct parasite inoculum for each strain to reach the chronic phase when the sera were collected. Thus, to evaluate whether the differences in reactivity observed in the ELISA experiments were dependent on the inoculum, we tested the reactivity of sera from mice infected with 50, 100, or 500 CL Brener trypomastigotes (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The T. cruzi isolates showed variable behavior in experimental infections in mice, promoting low parasitemia, virulence and pathogenicity, which is compatible with the low parasitemia and morbidity profi le of CD in humans and with the poor performance of diagnostic methods in the region (43) . In mice, the frequency of resistance to benznidazole among the TcIV isolates was signifi cantly higher than in the TcI isolates (35) . To date, TcII, TcV and TcVI, which are the predominant DTUs in humans and in domiciliary and peri-domiciliary vectors in the Southern Cone (41) (42) of the continent, have not been reported in Amazonas.…”
Section: Chagas Disease In the State Of Amazonasmentioning
confidence: 89%
“…Studies in Amazonas have demonstrated the presence of DTUs TcI, TcIII and TcIV in the parasite sylvatic transmission cycle (33) (34) (35) (38) . TcIV predominates among orally transmitted acute human cases (34) , and TcI predominates among the isolated and chronic cases (35) (38) , suggesting their association with different transmission profiles. The T. cruzi isolates showed variable behavior in experimental infections in mice, promoting low parasitemia, virulence and pathogenicity, which is compatible with the low parasitemia and morbidity profi le of CD in humans and with the poor performance of diagnostic methods in the region (43) .…”
Section: Chagas Disease In the State Of Amazonasmentioning
confidence: 99%
“…This may be attributed in part to the genetic aspects and immune competence of local human populations (Ayo et al, 2013; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Nogueira et al, 2012) and/or to parasite genetic heterogeneities. The latter hypothesis finds support in animal studies (that do not strictly recapitulate Chagas disease-associated physiopathologies), which revealed inter-strain variations in complex phenotypes such as parasitemia, virulence, tissue tropism/distribution and pathogenicity (Figure 1) (Andrade et al, 1999; Andrade, 1990; Camandaroba, Pinheiro Lima and Andrade, 2002; de Souza et al, 1996; Laurent et al, 1997; Monteiro et al, 2013; Revollo et al, 1998; Roellig et al, 2010). However, generalized conclusions are difficult to derive, particularly because these epidemiological studies might have been skewed by a number of intrinsic shortcomings.…”
Section: Trypanosoma Cruzi An 'All-wheel Drive' Parasitementioning
confidence: 96%